Ekonomický vývoj podniků financovaných rizikovým kapitálem - Platenková, Kamila (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Tato diplomová práce se zabývá hodnocením ekonomického stavu a vývoje v zadaných podnicích, které jsou financovány rizikovým kapitálem. Ekonomický vývoj podniků je podrobován vybraným ukazatelům finanční analýzy. Teoretická východiska práce popisují vybrané aspekty finanční analýzy a rizikového kapitálu. Analytická část se zaměřuje na vývoj ekonomické situace v podnicích pomocí vybraných ukazatelů a navrhuje možné zlepšení ekonomického vývoje společností. Závěr práce porovnává vývoj ukazatelů podniků a poskytuje možná řešení jejich situace.

This dissertation is looking into evaluation of the economical situation and development of the assigned companies which are financed by the high-risk capital. The economical development of the companies is subjected to selected indicators of the financial analysis. The theoretical solution of this dissertation is describing the particular aspects of the financial analysis and the high-risk capital. The analytical section is focusing on the development of the economical situation in the companies using the selected indicators and is proposing a possible improvement of the economical progress of the companies. Conclusion of this thesis is comparing development of the companies’ indicator and is providing its feasible solution.
Economic Development of Companies Financed by Venture Capital
Keywords: Podnik; ekonomický vývoj; rizikový kapitál; financování podniku; finanční analýza; Business; economic development; venture capital; corporate finance; financial analysis